Determinants of online takaful purchase behaviour among M40 income earners - Nur Natasya Farhana Amri; Nur Ridani Mohd Salam; Nur Saffa Atikah Roslan; Nur Solihah Abdul Halim Koh (2023)
Delivering a Takaful product online aims to boost competitive growth in the Islamic insurance industry, which was based on Takaful firms' ability to prosper in the highly developed insurance market. However, Takaful or insurance coverage ownership was 22% of Malaysians in the M40 income earners. There were numerous significant determinants that contribute to online takaful purchase behaviour among M40 income earners. The goal of this study is to identify the relationship between self-efficacy, social influence, and online takaful purchasing behaviour among M40 income earners. The data for this study were collected quantitatively using a set of questionnaires distributed evenly among 384 respondents in Kota Bharu, Kelantan, via Google Form. The data was analysed using the Statistical Package for Social Science (SPSS). According to the findings of the questionnaire, online takaful purchase behaviour among M40 income earners is positively correlated with selfefficacy and social influence. At the end of this study, the researcher was mention that all the determinants have the impaction towards online takaful purchase behaviour among M40 income earners. This study also emphasised the implications of the findings for future research as well as the study's limitations.